Synergistic effect of activated carbon and encapsulated trace element additive on methane production from anaerobic digestion of food wastes – Enhanced operation stability and balanced trace nutrition. (April 2019) - Zhang, Le; Loh, Kai-Chee
Graphical abstract: Highlights: Synergy of activated carbon and encapsulated trace element additive was studied. Joint addition increased average methane yield by 12–23%. Additives increased Ni bioavailability by 11–23% by increasing water soluble form. Growth of hydrolytic, acidogenic and acetogenic bacteria selectively enhanced. Joint addition enriched beneficial methanogens like Methanolinea and Methanosarcina. Abstract: Laboratory semi-continuous anaerobic digestion (AD) experiments were performed to investigate the effects of different supplements on the AD performance of food waste, specifically activated carbon (AC), encapsulated trace element additive (ETEA) and a combination of AC + ETEA. Results indicated that the operation stability of AD was enhanced through the addition of the additives. Compared with the control digester without any additive, AC, ETEA, and AC + ETEA increased the average methane yield by 34%, 22% and 50%, respectively. Chemical speciation analyses indicated that AC + ETEA supplementation increased the proportion of water soluble form of Ni by 11–23%, compared to ETEA single addition. Real-time PCR analyses showed that AC and ETEA supplementation synergistically facilitated the growth of bacterial and archaeal communities. Microbial community structure analysis revealed that AC + ETEA favored the enrichment of hydrolytic, acidogenic and acetogenic bacteria and methanogens.